Development of a Monocyte Activation Test as an Alternative to the Rabbit Pyrogen Test for Mono- and Multi-Component Shigella GMMA-Based Vaccines - Carson, Danielle (Microorganisms, 2021)
Generalised modules for membrane antigens (GMMA)-based vaccines comprise the outer membrane from genetically modified Gram-negative bacteria containing membrane proteins, phospholipids and lipopolysaccharides. Some lipoproteins and lipopolysaccharides are pyrogens; thus, GMMA-based vaccines are intrinsically pyrogenic. It is important to control the pyrogenic content of biological medicines, including vaccines, to prevent adverse reactions such as febrile responses. The rabbit pyrogen test (RPT) and bacterial endotoxin test (BET) are the most commonly employed safety assays used to detect pyrogens. However, both tests are tailored for detecting pyrogenic contaminants and have considerable limitations when measuring the pyrogen content of inherently pyrogenic products. We report the adaptation of the monocyte activation test (MAT) as an alternative to the RPT for monitoring the pyrogenicity of Shigella GMMA-based vaccines. The European Pharmacopoeia endorses three MAT methods (A–C). Of these, method C, the reference lot comparison test, was identified as the most suitable. This method was evaluated with different reference materials to ensure parallelism and consistency for a mono- and multi-component Shigella GMMA vaccine. We demonstrate the drug substance as a promising reference material for safety testing of the matched drug product. Our results support the implementation of MAT as an alternative to the RPT and use of the defined parameters can be extended to GMMA-based vaccines currently in development, aiding vaccine batch release.